Low-iodine 40-keV virtual monoenergetic CT angiography of the lower extremities - Fahrni, Guillaume; Mingas, Thomas; Deliessche, Arthur; Hraichi, Smail; Rotzinger, David C.; Si-Mohamed, Salim A.; Boccalini, Sara; Douek, Philippe (Frontiers in Cardiovascular Medicine, 2023)
Purpose: To evaluate a reduced iodine volume protocol for lower extremity CT angiography (CTA) using dual-energy CT (DECT). Materials and Methods: This retrospective study included consecutive patients who underwent lower extremity CTA from June to December 2022. A 10 ml 1:1 mixed test bolus was performed, followed by a 40 ml full bolus at a 2.5/s injection rate, using 400 mg/ml iodine contrast media. Conventional and 40 keV virtual monoenergetic images (VMI) were reconstructed. For both reconstructions, five main artery segments were assessed with a 3-point image quality score as well as quantitative attenuation, signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) measurements with diagnostic quality thresholds (respectively >150 HU and >3). Results: Forty patients were included in the study (mean age 68 ± 12 yo). 200 artery segments were assessed. Median qualitative image scores were 3 [IQR, 3, 3] for both reconstructions. 40 keV VMI upgraded qualitative scores for 51 (26%) of patients, including 9 (5%) from nondiagnostic to diagnostic quality. 40 keV VMI obtained attenuation and CNR diagnostic quality for respectively 100% and 100% of segments, compared with 100% and 100% for conventional images (p < 0.001). Distal artery segments showed the most differences between 40 keV VMI and conventional images. Conclusion: A low-iodine lower extremity CTA protocol is feasible, with 40 keV virtual monoenergetic spectral reconstruction enabling maintained diagnostic image quality at the distal artery segments.